2008
DOI: 10.1890/07-0550.1
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Climate Change and Its Impacts on the Ecology of the North Atlantic

Abstract: Abstract. Arctic climate change from the Paleocene epoch to the present is reconstructed with the objective of assessing its recent and future impacts on the ecology of the North Atlantic. A recurring theme in Earth's paleoclimate record is the importance of the Arctic atmosphere, ocean, and cryosphere in regulating global climate on a variety of spatial and temporal scales. A second recurring theme in this record is the importance of freshwater export from the Arctic in regulating global-to basin-scale ocean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 89 publications
(121 reference statements)
2
86
0
1
Order By: Relevance
“…These correlations might indicate a specific role of the Arctic area, which has been shown to influence both North Pacific and North Atlantic ecosystems [76,77].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These correlations might indicate a specific role of the Arctic area, which has been shown to influence both North Pacific and North Atlantic ecosystems [76,77].…”
Section: Resultsmentioning
confidence: 97%
“…The first of these resulted in the Great Salinity Anomaly of the 1990s, characterized by the discharge of relatively low-salinity water from the Arctic Ocean into the North Atlantic through the Canadian Arctic Archipelago and Fram Strait (between Greenland and Svalbard) [41,76]. North Atlantic circulation (increased discharge of relatively low-salinity water into the North Atlantic, and redirection of the shallow, low-salinity outflow from the Arctic Ocean mainly through the Labrador Sea [41,76]). The Pacific Ocean circulation is also influenced by the Arctic circulation [97] and by the AO.…”
Section: Discussionmentioning
confidence: 99%
“…that have been documented since the late 1960s (Belkin et al, 1998;Belkin, 2004;Greene et al, 2008). All of these , 1997;Dukhovskoy et al, 2006;Mclaughlin et al, 2011).…”
Section: E R I C a H E A D P E T E R S M I T H A N D A L E S S A mentioning
confidence: 99%
“…Despite the relatively low levels of warming that have occurred in our study area to date (Prowse et al, 2006a), recent models have suggested that the Labrador Sea may be particularly sensitive to warming-related shifts in circulation and salinity, and this may impact inland waters in northern Labrador and Québec (Greene et al, 2008). The results of our study indicate the importance of monitoring environmental variables along the full extent of the hierarchical framework to detect impacts from future warming.…”
Section: Implications For Monitoring and Management Of Arctic Streamsmentioning
confidence: 68%